Odtwarzalność w granicach pary przekładowej - Wierzchoń, Piotr (Przegląd Rusycystyczny, 2007)
REPRODUCIBILITY WITHIN THE CONFINES OF TRANSLATION UNITS Summary The article presents a multi-word unit retrieval procedure set against the background of other computer science-based methods for the retrieval of multi-word idiomatic units (methods: T-score, Mutual Information, n-gramming etc. and, on the other hand, observation of structural idiomaticity determinants). In Polish language and contrastive Polish-Russian linguistics major inspirations concerning the description of idiomatic combinations (multi-word units, such as przepraszamy za usterki, czwórka z Liverpoolu, lista Wildsteina etc.) were proposed by A. Bogusławski and their extensive development was carried out in W. Chlebda’s group (retrieval, collection, position of multi-word units in cultural contexts, reconstruction of authorship, semantic interpretation and even translation suggestions). Automatic methods can be divided into advanced statistical methods (n-gramming, see Yamamoto, Church 2001, Buczyński 2004) and “infantile” approaches (e.g. so-called quotation retrieval, cf., among others, Wierzchoń 2005). The present article puts forward a new method for the retrieval of idiomatic combinations applied to a specifi c text, that is, a reverse order index of transla-tion units. The reverse index lists translation pairs made up of Russian and Polish language segments (words, phrases etc.) ordered according to the sequence of the Russian and Polish alphabet, respectively. Reproducibility of their components is searched for within the confi nes of those pairs. The retrieval method in question to some extent uses ready (lexicographically compiled) multi-word units, the improvement being, however, the development of their presentation in order to enable relatively uncomplicated observation of the reproducibility of translation pair components. ВОСПРОИЗВОДИМОСТЬ В ПРЕДЕЛАХ ПЕРЕВОДНЫХ ПАР Резюме Статья содержит краткий обзор методов эксцерпции устойчивых сверхлексемных об-разований, используемых в информатических кругах (напр., T-score, Mutual Information, n-gramming, анализ структурных показателей идиоматичности и т.п.). Предлагая еще одну процедуру выделения устойчивых сверхлексемных образований, автор исходит из идей, предложенных на почве польского и сопоставительного польско-русского языкознания Анджеем Богуславским (концепция единиц языка типа przepraszamy za usterki, czwórka z Liverpoolu, lista Wildsteina) и развитых Войцехом Хлебдой (вопросы эксцерпции, связи с культурным контекстом, восстановления авторства, семантической интерпретации, возможности перевода и т.п.). Автоматические методы можно разделить на продвинутые статистические (n-gramming — Yamamoto, Church 2001, Buczyński 2004) и «инфантильные» подходы (эксцерпция «по кавычкам»; см. Wierzchoń 2005). Дополнительный метод эксцерпции устойчивых сверхлексемных образований основан на анализе специфического текста, которым является обратный словарь переводных пар, разработанный автором. В пределах этих пар и ведется поиск воспроизводимости их компонентов. Эксцерпция сводится, таким образом, к использованию готовых, т.е. лексикографически уже разработанных, устойчивых сверхлексемных образований, новой же является форма их демонстрации, позволяющая вести несложные наблюдения за воспроизводимостью компонентов переводных пар.